"A Two-Way Street": Adjunct Faculty's Learning from and with Students about Subject Matter. Issue 1 (2nd January 2022) - Bolitzer, Liza Ann
Abstract: Within the work of teaching, college faculty can develop stronger understandings of both their subject matter and their students' socio-cultural understandings of that subject matter. Such learning is particularly important for faculty that teach today's students, who bring unprecedented racial, ethnic, socio-economic and age diversity to higher education. By engaging their students' diverse identities and life experiences, faculty can potentially deepen both their students understanding of subject matter and their own. To better understand this learning for adjunct faculty, who are the majority of faculty in higher education today, this study examines how and what adjunct faculty can learn about their students and subject matter within their work as teachers. Drawing on interviews and classroom observations of 19 adjunct instructors of general education courses at two institutions that serve a diverse student population, it yields insights into the ways in which adjunct faculty may learn about their students' lives and identities, the subject matter of their courses, and the potential connections between that subject matter and their students.